DNA Topoisomerases of Leishmania Parasites; Druggable Targets for Drug Discovery - Reguera, Rosa M; Elmahallawy, Ehab K; García-Estrada, Carlos; Carbajo-Andrés, Rubén; Balaña-Fouce, Rafael (Current medicinal chemistry, 2019)
DNA topoisomerases (Top) are a group of isomerase enzymes responsible for controlling the topological problems caused by DNA double helix in the cell during the processes of replication, transcription and recombination. Interestingly, these enzymes have been known since long to be key molecular machines in several cellular processes through overwinding or underwinding of DNA in all living organisms. Leishmania, a trypanosomatid parasite responsible for causing fatal diseases mostly in impoverished populations of low-income countries, has a set of six classes of Top enzymes. These are placed in the nucleus and the single mitochondrion and can be deadly targets of suitable drugs. Given the fact that there are clear differences in structure and expression between parasite and host enzymes, numerous studies have reported the therapeutic potential of Top inhibitors as antileishmanial drugs. In this regard, numerous compounds have been described as Top type IB and Top type II inhibitors in Leishmania parasites, such as camptothecin derivatives, indenoisoquinolines, indeno-1,5- naphthyridines, fluoroquinolones, anthracyclines and podophyllotoxins. The aim of this review is to highlight several facts about Top and Top inhibitors as potential antileishmanial drugs, which may represent a promising strategy for the control of this disease of public health importance.